Effect of maize plant detasseling on grain yield, tolerance to high plant density and drought stress - Sangoi, Luis; Jonathan Salvador, Ricardo (Pesquisa Agropecuaria Brasileira, 1998)
Maize (Zea mays L.) is unusually susceptible to drought and high density stresses at flowering. In part, this is related to its monoecial floral organization, which favors development of the male inflorescence, assuring pollen production and dispersion at the expense of ear and silk development. This field experiment was conducted to evaluate the potential benefits of eliminating the tassel, in terms of increasing grain yield and maize tolerance to high plant density and drought stress. Four genotypes were studied in 1993 and 1994 in Ames, IA, US. Each genotype was evaluated at the densities of 25,000 and 75,000 pl ha-1. Tassel removal, either partial or total, did not significantly enhance grain yield and components, regardless of plant density or cultivar. Grain yield was higher at 75,000 pl ha-1 than at 25,000 pl ha-1 in both years. No difference in grain yield was observed between male-sterile and fertile counterparts. The absence of drought stress, and the mechanical damage to the leaves during tassel removal contributed to prevent a positive response of grain yield to tassel suppression.